Pengaruh Supervisi Kepala Sekolah dan Etos Kerja Guru terhadap Disiplin Guru di MTs Se-Kecamatan Pinang Kota Tangerang - Nurdin Nurdin; Zubairi Zubairi; Alexander Guci (LP. Ma'arif Janggan Magetan, 2023)
This research aims to determine the influence of principal supervision and teacher work ethic on teacher discipline at MTs in Pinang District, Tangerang City. The method used in this research is a survey research method. The variables in the research consist of two independent variables, namely supervision of the madrasa head as a variable (X1), teacher work ethic as a variable (X2), and one dependent variable, namely teacher discipline as a variable (Y). The sample in this study was 102 teachers taken randomly. Based on the results of the regression and influence analysis, it is known that the supervision of madrasah heads has an influence on teacher discipline. Based on the t test analysis, it shows that the t value is 15.056. After comparing, it turns out that the tcount value is greater than ttable (15.056 > 2.625), so it can be concluded that the supervision of the madrasa head (X1) has a significant effect on teacher discipline (Y). The teacher's work ethic has an influence on teacher discipline. The t test analysis shows that the tcount value is 15.456, after comparing it turns out that the tcount value is greater than ttable (15.456 > 2.625), so it can be concluded that teacher work ethic (X1) has a significant effect on teacher discipline. The results of the regression and influence analysis show that the supervision of the madrasa head and the teacher's work ethic have an influence on teacher discipline. Based on the results of the F test, it is known that the calculated F value is 259.96. After comparing, it turns out that the calculated F value is greater than the F table (259.96 > 19.486), so it can be concluded that the supervision of the madrasa head (X1) and the teacher's work ethic (X2) together they have a very significant effect on teacher discipline (Y). Based on the results of the analysis, it can be seen that the influence of madrasa head supervision (X1) and teacher work ethic (X2) on teacher discipline (Y) obtained a coefficient of determination of 0.840. This means that the supervision of the madrasa head (X1) and the teacher's work ethic (X2) together have an influence of around 84% on teacher discipline in MTs throughout Pinang District, Tangerang City. Based on the findings of the research results showing that there is a direct positive and significant influence of the supervision of madrasa principals and the work ethic of teachers together on the discipline of MTs teachers throughout Pinang District, Tangerang City, in order to improve the quality of education, it is recommended: School principal supervision of teachers should be carried out optimally through monitoring, assessment and guidance by planning, implementing and following up, so that teachers become aware of regulations, both those made by the school and the government. Enforcement of school discipline can be done through optimizing the supervision of madrasah heads towards teachers and increasing teacher work ethic.